Clinical presentation and treatment of thrombotic thrombocytopenic purpura - analysis of recent diagnostic and therapeutic methods - Szwech, Jan; Matczak, Mateusz; Jasiński, Karol; Broda, Aleksandra; Hoksa, Kacper; Jodłowski, Krzysztof; Dubniewicz, Ewa; Majewska, Paula; Staszek, Alicja; Łoskot, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction Thrombotic thrombocytopenic purpura (TTP) is a rare hematologic disease caused by reduced ADAMTS13 (A disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13) activity. This disease can lead to a variety of symptoms and be difficult to diagnose. Correct diagnosis is very important to reduce mortality and initiate appropriate treatment. New treatment methods may offer better chances of survival from this potentially fatal disease. Aim of the study The aim of the article was to evaluation of different diagnostic pathways and the effectiveness of treatment of thrombotic thrombocytopenic purpura. Drawing the attention of the medical community to the discussed issue. Highlighting the importance of the issue due to the high mortality rate in the absence of treatment. Materials and methods The article was prepared by analyzing multiple databases, including PubMed, Google Scholar, and Elsevier covering the period from 2018 to 2024. Conclusion Thrombotic thrombocytopenic purpura (TTP) is a rare but serious disease, especially if appropriate treatment is not initiated. There is need a special attention to TTP, as treatment needs to begin even before a definitive diagnosis is established, due to the lengthy wait for laboratory results. Although modern biological drugs are available, further research is needed to streamline treatment methods and provide new therapeutic opportunities.